Influence of planting ratio and plant spacing on hybrid seed yield and quality in tropical carrot (Daucus carota) cv. Pusa Vasuda - SUTRADHAR, HRISHIKESH; PANDITA, V K; TOMAR, B S; YADAV, R N (The Indian Journal of Agricultural Sciences, 2023)
The present experiment was carried out to investigate the influence of planting ratio and plant spacing on hybrid seed yield and quality in carrot (Daucus carota L.) hybrid Pusa Vasuda at SPU, ICAR-IARI, New Delhi during 2014-15 and 2015-16. The experiment consisted of two different planting ratio (1:4 and 1:6) of pollen parent and seed parent and five plant spacing, viz. 60 cm × 20 cm, 60 cm × 30 cm, 60 cm × 40 cm, 60 cm × 50 cm and 60 cm × 60 cm. The results revealed that planting ratio and plant spacing had a significant effect on seed yield. Higher seed yield/ha (380.10 kg) was obtained in a planting ratio of 1:6 with closer plant spacing of 60 cm × 20 cm and it reduced significantly with increasing plant spacing. The planting ratio and spacing had no influence on seed quality trait was at par within the planting ratio and spacing. However, 1000 seed weight was significantly reduced with decreasing plant spacing. Thus, to obtained higher seed yield a planting ratio of 1:6 and a plant spacing of 60 cm × 20 cm should be recommended for hybrid seed production of carrot cv. Pusa Vasuda under Delhi conditions during rabi season.